Adsorption and possibility of separation of heavy metal cations by strong cation exchange resin - Hanna Vasylyeva (Elsevier, 2021)
This work is devoted to the study of the adsorption of strontium, yttrium, and zirconium ions by the strong acid cation exchange resin Dowex HCR-s/s. The adsorption of strontium, yttrium, and zirconium ions in batch and dynamic conditions from individual solutions of the studied elements, as well as from their mixture, was studied. It was shown that the dependences of the adsorption of strontium, yttrium, and zirconium ions on agitation time fit well with the pseudo-first-order and Elovich equations. Equilibrium adsorption of all three cations can be described with Langmuir's theory. Column adsorption has shown that Dowex HCR-s/s adsorb all three investigated cations from the acidic medium. The inductively coupled plasma mass spectrometry (ICP-MS) proves that separation of these cations using Dowex HCR-s/s is possible only in highly dilute solutions at a concentration of 10 ng/ml of each element. The basis of separation will be a higher rate of adsorption of tetravalent zirconium, compared with strontium and yttrium. As the concentration of the investigated elements increases to 100 ng/ml, all three cations are adsorbed by the resin in equal amounts and can be separated only using special eluents, such as Ca-EDTA.